The impediments to the application of International Financial Reporting Standards from the point of view of academics and professionals in the Sudan - Elfaki, Alfateh Alamin Abdalrahim; Al Hassan, Mahjoub Al Tayeb Mohamed (Archives of Business Research, 2018)
The study the impediments to the application of International Financial Reporting Standards from the point of view of academics and professionals in Sudan, where the problem in question and the main obstacles to the application of international accounting standards in Sudan? Branched out by a number of questions including; is there a specific mechanism to commit companies in Sudan to apply international accounting standards? Is the organization of accounting and auditing in Sudan identify training needs necessary to complete the process of transition to international standards? Do installations in Sudan is ready financially and to complement the process of transformation? What is the role of the accounting curricula to improve the application of International Financial Reporting Standards?. The study aimed at the statement of the challenges and constraints facing the application of International Financial Reporting Standards in the Sudan, and to clarify the mechanism for the application of international standards and the associated requirements of joining the International Federation of Accountants (IFAC) system, and the reflection of the application of international standards of accounting and auditing the accounting curriculum development in higher education institutions (the impact on accounting taught scientific movement in accounting). The inductive and deductive approach was used, as was the use of the questionnaire as a tool for data collection. The researchers reached to many results, the most important factors affecting the internal environment directly impact in the application of International Financial Reporting Standards these factors in many of the most prominent elements of the administrative policies and the size of the business of the company and its capital, and the prevailing culture, the size of the funding for the transformation process and the application of international standards and the extent of readiness as well as the experiences and competencies necessary accounting full transformation. The failure to meet the requirements of the external environment was largely on the application of international accounting standards, the most important of these requirements in the commitment to the application of standards as a condition of joining the International Federation of Accountants (IFAC) in accordance with the statements of membership obligations (SMO,s) that development and performance, add it to join the World Trade Organization, global and regional markets. The study also recommended many of the recommendations, including attention to the training of accountants, and review of accounting curricula in higher education